1999
DOI: 10.1038/sj.onc.1202509
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the BRCA1 promoter region in sporadic breast and ovarian cancer: correlation with disease characteristics

Abstract: Reduced expression of BRCA1 has been reported in sporadic breast cancer, although the mechanisms underlying this phenomenon remain unclear. Abnormal methylation leading to silencing of tumour suppressor genes has been implicated in tumorigenesis in a wide range of sporadic cancers. Therefore, we sought to determine the frequency of methylation within the BRCA1 promoter region in a large group of sporadic invasive breast (n=96) and ovarian (n=43) carcinomas using Southern analyses. Overall, methylation was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
183
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(193 citation statements)
references
References 29 publications
(41 reference statements)
9
183
1
Order By: Relevance
“…A growing number of studies have linked the decreased expression of the BRCA1 gene to both the initiation and progression of sporadic breast cancer (Thompson et Jarvis et al, 1998;Ozcelik et al, 1998;Catteau et al, 1999). Characterizing the elements regulating the BRCA1 promoter is a crucial part of understanding how this change in expression occurs at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies have linked the decreased expression of the BRCA1 gene to both the initiation and progression of sporadic breast cancer (Thompson et Jarvis et al, 1998;Ozcelik et al, 1998;Catteau et al, 1999). Characterizing the elements regulating the BRCA1 promoter is a crucial part of understanding how this change in expression occurs at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…A series of papers has also suggested that methylation of the BRCA1 promoter may be a signi®cant factor in decreasing BRCA1 expression in sporadic breast tumors, possibly through inactivation of a CREB site (Mancini et al, 1998). However, methylation can account for decreased BRCA1 expression only in a subset of sporadic breast cancer samples (Magdinier et al, 1998;Dobrovic and Simpfendorfer, 1997;Rice et al, 1998;Mancini et al, 1998;Catteau et al, 1999). Overall, these results suggest that sporadic breast cancer may result from defects in the genes regulating the BRCA1 promoter, or that transformation leads to a concomitant down regulation of BRCA1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to inherited mutations, other means of regulating BRCA1 function may be important in sporadic tumors. The gene is down-regulated at the transcriptional level in sporadic cancer (Catteau et al, 1999;Mancini et al, 1998;Wilson et al, 1999) and the BRCA1 protein becomes mislocalized following infection with certain transforming viruses (Maul et al, 1998). There are currently no models which allow testing for the consequences of individual mutations in the human BRCA1 gene in an intact animal system.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of sequence is not randomly distributed, but concentrated to GC-enriched islands (CpG islands), which usually situates at the position in or near transcription regulatory region. Sensitivity of methylation on all CpG is not the same, and the methylation level at the site of CpG can be changed [10][11][12] . Prevalent hypomethylation and local hyper methylation exist in genome of cancer tissue, for example, hypermethylation on promoters of p16, E-cadherin, and genes encoding hormone receptors and genes of DNA repair, and genes inhibiting the genesis of blood vessels may induce the absent or low expression of these gene and improve the oncogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%